Assessment of Annual Sediment Load Using Mike 21 Model in Khour Al-Zubair Port, South of Iraq - Dakheel, Ahmed A.; Al-Aboodi, Ali H.; Abbas, Sarmad A. (Basrah Journal for Engineering Sciences, 2022)
Although estuarine locations provide natural safety and protection for the construction of harbours and other infrastructure, they are prone to natural filling due to sediment settlement. As a result, dredging is required regularly to keep navigation channels and harbours safe and functional. A numerical model has been developed in this study to compute annual sediment load in Khour Al-Zubair Port, South of Iraq, setting up a MIKE 21 FM model. MIKE 21 FM was developed by the Danish Hydraulic Institute (DHI) where provides the capability of simulation of a hydrodynamic model (HD) coupled with the mud transport model (MT). The model operates with an unstructured mesh of triangles and quadrilateral elements of different sizes. Field and experimental data were provided during two periods (Neap and Spring) for calibration and verification process. According to the sensitivity analysis results, it is clear that the settling velocity is an essential parameter. Based on the results of the calibrated model, there is annual sedimentation of 1220500.64 tons/year. The primary deposition took place in the meandering of the Khour Al-Zubair estuary and behind the piers.